VIRTUAL ASSISTANTS: How they help people with physical disabilities - Beatris Marques, Dandara; Lucca Filho, Joao de (Revista Interface Tecnológica, 2023)
This article analyzes the implications and role of virtual assistants in helping people with disabilities. After a literature review, data on the use of these technologies by people with disabilities were obtained, and the benefits provided were measured. Virtual assistants, VAs, represent a potential tool to help people with disabilities face everyday challenges and improve their quality of life. These technologies allow people to perform daily tasks more easily and independently, promoting inclusion and assistance. They helped with tasks like identifying a food, expiration date and even being in danger by triggering help; they work through voice commands and even video if a person stops in front of the virtual assistant device. In conclusion, it highlights the importance of investing in assistive technologies to ensure social inclusion and equal opportunities for all people, regardless of their physical and sensory limitations. It is essential to respect fundamental rights in human interactions as a way to promote inclusion.